In vitro culture of the zoonotic nematode Anisakis pegreffii (Nematoda, Anisakidae) - Ivona Mladineo; Artemis Charouli; Filip Jelić; Anand Chakroborty; Jerko Hrabar (Parasites & Vectors, 2023)
Abstract Background Anisakiasis is a foodborne disease caused by the third-stage larvae (L3) of two species belonging to the genus Anisakis: Anisakis pegreffii and Anisakis simplex sensu stricto. Both species have been the subject of different -omics studies undertaken in the past decade, but a reliable in vitro culture protocol that would enable a more versatile approach to functional studies has never been devised. In nature, A. pegreffii shows a polyxenous life-cycle. It reproduces in toothed whales (final host) and disseminates embryonated eggs via cetacean faeces in the water column. In the environment, a first- (L1) and second-stage larva (L2) develops inside the egg, and subsequently hatched L2 is ingested by a planktonic crustacean or small fish (intermediate host). In the crustacean pseudocoelom, the larva moults to the third stage (L3) and grows until the host is eaten by a fish or cephalopod (paratenic host). Infective L3 migrates into the visceral cavity of its paratenic host and remains in the state of paratenesis until a final host preys on the former. Once in the final host’s gastric chambers, L3 attaches to mucosa, moults in the fourth stage (L4) and closes its life-cycle by becoming reproductively mature. Methods Testing two commercially available media (RPMI 1640, Schneider’s Drosophila) in combination with each of the six different heat-inactivated sera, namely foetal bovine, rabbit, chicken, donkey, porcine and human serum, we have obtained the first reliable, fast and simple in vitro cultivation protocol for A. pegreffii. Results Schneider’s Drosophila insect media supplemented with 10% chicken serum allowed high reproducibility and survival of adult A. pegreffii. The maturity was reached already at the beginning of the third week in culture. From collected eggs, hatched L2 were maintained in culture for 2 weeks. The protocol also enabled the description of undocumented morphological and ultrastructural features of the parasite developmental stages. Conclusions Closing of the A. pegreffii life-cycle from L3 to reproducing adults is an important step from many research perspectives (e.g., vaccine and drug–target research, transgenesis, pathogenesis), but further effort is necessary to optimise the efficient moulting of L2 to infective L3. Graphical Abstract